Alpha-1 antitrypsin deficiency: Pathophysiologic features and the importance of screening. Issue 12 (December 2016) - McCosh, Kelly
Abstract : ABSTRACT: Alpha-1 antitrypsin deficiency is an inherited disorder that may lead to early development of emphysema and also can cause serious hepatic disease. Because the condition is underrecognized, diagnosis may be delayed. This article aims to increase awareness about alpha-1 antitrypsin deficiency and screening guidelines that can help primary care providers identify patients early for better outcomes.